Knowledge and Practice of Healthcare Personnel Regarding Disinfection and Sterilization of Surgical Instruments at a Tertiary Level Hospital in Rajshahi - Islam, Md Tahmidul; Haque, Md Jawadul; Salauddin, Gazi; Sarker, Lamia (Northern International Medical College Journal, 2025)
Background: The process of sterilization involves eliminating or completely destroying all germs, including bacterial spores. Controlling and preventing infections is a crucial component of providing safe patient care. Objective: The objective of this study was to assess the knowledge and practice of healthcare personnel regarding disinfection and sterilization of surgical instruments at tertiary level hospitals in Rajshahi. Methodology: This cross-sectional type of descriptive study was conducted over a period of 1 year in the Department of Community Medicine, Rajshahi Medical College, Rajshahi. In this study, study population was healthcare personnel who were working in different tertiary level hospitals in Rajshahi. The knowledge and practice of healthcare personnel regarding disinfection and sterilization of surgical instruments were done by semi-structured questionnaire with score 1 for Yes and 0 for No answer. Health Care Workers (HCWs) score equal to or above 50% were considered having safe knowledge and instrument processing practice (IPP) and score below 50% having unsafe knowledge and IPP on disinfection and sterilization of surgical instruments. The data were analyzed via SPSS (version 24.0) and p < 0.05 was considered statistically significant. Result: The study population included 236 healthcare workers, of which 142 (60.2%) had safe knowledge and 94 (39.8%) had unsafe knowledge, while, 131 (55.5%) were practicing safely and 105 (44.5%) were practicing unsafely. The majority of healthcare workers with safe knowledge and practice were in the age range of 20-25 years. The relationship between healthcare workers’ knowledge and practice with age, sex, marital status, professional status, working departments and duration of service were not statistically significant ( p > 0.05 each). On the other hand, the relationship between healthcare workers’ infection prevention training, awareness on infection prevention, availability of poster, standard operating procedure (SOP) or guideline and vaccination against hepatitis B were statistically significant ( p < 0.05 each). Conclusion: The findings of this study indicated that the way medical staff members clean and store equipment was unsafe. HCWs must be more knowledgeable about infection prevention and control (IPC) and possess superior operational abilities if healthcare facilities are to be free of infections. Northern International Medical College Journal Vol. 15 No. 1-2 July 2023-January 2024, Page 655-659